HEGEMONI EKONOMI KELAS BORJUIS DENGAN BURUH DALAM NOVEL GERMINAL KARYA EMILE ZOLA - Mariam Ulfa; Sri Sulistiani; Ana Yuliati (Jurnal Sastra Aksara, 2020)
This paper discusses the comparison of the bourgeoisie and the working class in terms of social and economic life. Emile Zola's novel Germinal represents the life of the workers and their misery compared to the life of the bourgeoisie. For decades the workers have not been able to improve the standard of living and the economy for decades, while the bourgeoisie has always lived in sufficiency and economic life from generation to generation. The workers who are hegemonized by the bourgeoisie are economically alive in limitations, children who are teenagers who should go to school must accept being laborers because of economic conditions. To create a bourgeoisie because of its wealth does not do manual labor and is able to attend high school. The novel Germinal contains literary works which are able to provide education about economics and implicitly provide a movement towards a better direction to improve the standard of living so that it is not always controlled by the bourgeoisie.